Why people make friends: The nature of friendship. Issue 1 (18th November 2020) - Apostolou, Menelaos; Keramari, Despoina; Kagialis, Antonios; Sullman, Mark
Abstract: Friendship constitutes an important facet of human behavior, and the current research investigated the reasons that motivate people to make friends. First, a combination of qualitative research methods were used to identify 41 perceived reasons why people make friends. Using a sample of 1, 316 Greek‐speaking participants, these reasons were classified into five broad factors. Participants indicated that the most important reasons for making friends were to receive social input, support, and because of someone else's good qualities. Sex differences and age effects were found in most factors. Finally, the five factors were classified into two broader domains, the first reflecting motivation to make a true friendship and the second to gain opportunistic benefits.